Short and medium term results in mitral valvuloplasty. Preliminary study - Julio César Echarte Martínez; Luis Roberto Llerena Rojas; Juan Prohías Martínez (ECIMED, 2014)
The results of the first six percutaneous mitral valvuloplasties (PMV) performed at the Hemodynamics Laboratorory of the Cuban Institute of Cardiology and Vascular Surgery are presented. Excepting a patient with a mitral area of 1,4 cm2, the rest had areas under 1 cm2 . A significant post-PMV increase (1,6 - 2,6 cm2) and a marked improvement of the functional class of the NYHA (from III-IV to I) were obtained in all cases. WILKINS? score ranged from 4 to 12 points. There was only an inguinal hematoma that was resolved without difficulties. It is concluded that PMV may be an efficient alternative in the treatment of patients with mitral stenosis in our environment.